Sturge Weber syndrome - Roka, Yam Bahadur (Nepal Journal of Neuroscience, 2019)
Sturge-weber syndrome is a type of neurocutaneous syndrome/ neurooculo cutaneous/ phakomatoses that is characterized by facial capillary Port Wine stain, leptomeningealangioma and glaucoma with a incidence of 1 per 20-50,000 live births. A case is reported that presented to the outpatient clinic with discharging wound over the left side of his head for a week. On examination he had a large left facial PW stain involving all the divisions of the Trigeminal nerve. Further examination revealed he had history of partial seizures since last 10 years with incomplete and irregular treatment. He also had right sided hemiatrophy of the limbs along with medial gaze deviation of the left eyeball. Skull skiagram was done outside which revealed calcifications in his left hemisphere and CT was then advised for his headache and seizure that revealed Left hemispheric Tram track calcifications along with cerebral atrophy and loss of cortical volume. EEG was unremarkable. He was managed with antibiotics for the scalp wound and discharged with Leveteracetam 1000 mg daily dose and asked to attend eye hospital for the reduced vision. With the PW stain, skin nodules, eye findings and the radiological features he was diagnosed as SWS and counseled for regular follow up, use of anti-epileptic medications, probable side effects and surgery for eye abnormalities.